Pengaruh Komunikasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Maya Graha Indah Tasikmalaya - Pinanti; Rahwana, Kusuma Agdhi; Arif (PT Maju Malaqbi Makkarana, 2023)
The purpose of this study was to determine the effect of communication and work discipline on the performance of employees at PT. MAYA GRAHA INDAH TASIKMALAYA, to determine the effect of communication on employee performance at PT. MAYA GRAHA INDAH TASIKMALAYA and to determine the effect of work discipline on employee performance at PT. MAYA GRAHA BEAUTIFUL TASIKMALAYA. The samples in this study were employees of PT. MAYA GRAHA INDAH TASIKMALAYA, totaling 41 people. This research was carried out by collecting data using questionnaire data collection techniques, then testing the data using multiple linear regression analysis. The results showed that communication and work discipline had a significant effect on employee performance at PT. MAYA GRAHA BEAUTIFUL TASIKMALAYA. No significant effect of communication on employee performance at PT. MAYA GRAHA BEAUTIFUL TASIKMALAYA. Work discipline has a significant effect on employee performance at PT. MAYA GRAHA BEAUTIFUL TASIKMALAYA.